1982
DOI: 10.1111/j.1467-6494.1982.tb00232.x
|View full text |Cite
|
Sign up to set email alerts
|

A re-view of cognitive mediators in learned helplessness

Abstract: The findings of Oakes and Curtis (1982), Tennen, Drum, Gillen, and Stanton (1982), and Tennen, Gillen, and Drum (1982) provide a challenge to learned helplessness theory's focus on cognitive mediators of the helplessness phenomenon. In response to these findings, Alloy (1982) argues that these studies do not challenge helplessness theory because they do not measure expected control and because they confuse necessary and sufficient causes of learned helplessness. Silver, Wortman, and Klos (1982) contend that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The question of specifying which aspects of controllability actively drive effects has been controversial. Some studies have suggested that differing rates of failure account completely for learned helplessness effects (Matute, 1994, 1995), while others have demonstrated that non-contingency is the crucial factor, and failure is unnecessary, in evoking learned helplessness (Oakes and Curtis, 1982; Tennen et al, 1982b; Kofta and Sedek, 1989). A third body of research suggests that these factors have additive or interactive effects on behavior (Koller and Kaplan, 1978; Tennen et al, 1982a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The question of specifying which aspects of controllability actively drive effects has been controversial. Some studies have suggested that differing rates of failure account completely for learned helplessness effects (Matute, 1994, 1995), while others have demonstrated that non-contingency is the crucial factor, and failure is unnecessary, in evoking learned helplessness (Oakes and Curtis, 1982; Tennen et al, 1982b; Kofta and Sedek, 1989). A third body of research suggests that these factors have additive or interactive effects on behavior (Koller and Kaplan, 1978; Tennen et al, 1982a).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that differing rates of failure account completely for learned helplessness effects (Matute, 1994, 1995), while others have demonstrated that non-contingency is the crucial factor, and failure is unnecessary, in evoking learned helplessness (Oakes and Curtis, 1982; Tennen et al, 1982b; Kofta and Sedek, 1989). A third body of research suggests that these factors have additive or interactive effects on behavior (Koller and Kaplan, 1978; Tennen et al, 1982a). In considering the results of Experiment 1, one possibility is that the ability to learn contingencies between actions and outcomes caused moderately reactive participants to respond adaptively to controllable stress, while the inability to learn contingencies eradicated this relationship for people exposed to uncontrollable stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review, Silver, Wortman, and Klos (1982) criticized these studies on three grounds. First, the relationship between experience with uncontrollable events and subsequent deficits may be mediated by a variety of factors, not just the expectation of response-outcome independence (e.g., Frankel & Snyder, 1978;Peterson, 1978;Tennen, 1982). Second, laboratory studies of human helplessness may be subject to demand characteristics that trivialize obtained results (Orne, 1962).…”
Section: Discussionmentioning
confidence: 99%
“…Even studies cited in support of a depressive attributional style (e.g., Golin et al, 1981) find that depression accounts for less than 3% of the observed variance in subjects' attributions (cf. Tennen, 1982). One explanation of the recent failures to replicate a depressive attributional style turns on the nature of the BDI, the inventory we used to measure depth of depression.…”
Section: Discussionmentioning
confidence: 99%